PUBLIC FINANCES AND MUNICIPAL FISCAL AUTONOMY: INCIDENCE IN COLOMBIAN PERFORMANCE - Anaya Yances, Freddy; Quiñones Agamez, Elkin (Revista Arbitrada Formación Gerencial, 2022)
The general objective of this article is to analyze the public finances and their incidence in the municipal fiscal autonomy and performance in Colombia. This paper is based on a qualitative approach based on document analysis. It is also based on the type of descriptive analytical research, has a non-transectional experience, specific characteristics of the following documents for public finance are shown: López, López and Meza (2014), in his research entitled Public Finances and Local Development. The case of the Municipalities of the department of Antioquia; Colombia (2001-2011), and Silva, Páez and Rodríguez (2008), in their research Public territorial finances. Territorial public administration program. Higher School of Public Administration, ESAP José Silva Ruiz. The results show that the categories in which the municipalities can be located range from the first to the sixth (plus a special one that corresponds to the capital cities), since the national government has sought that the municipalities consider increasing their own income making a greater effort in the generation of collection of the taxes that correspond to them. Likewise, the fiscal position was the instrument through which departments and districts participated in the current income of the nation and increased notably the tax capacity of territorial entities, however, in tax matters maintained the subordination of its regulatory power to the law.